2015
DOI: 10.1890/15-0242.1
|View full text |Cite
|
Sign up to set email alerts
|

An altitudinal cline in UV floral pattern corresponds with a behavioral change of a generalist pollinator assemblage

Abstract: Spatial variation in pollinator communities or behaviors can underlie floral diversification. Floral traits in the UV spectrum are common and mediate plant-pollinator interactions, but the role of pollinators in driving or maintaining their geographic variation has not been fully explored. We identify an altitudinal cline of increasing relative size of the UV bullseye pattern in Argentina anserina (Rosaceae) flowers, and assess whether pollination context contributes to clinal variation. At four sites that var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 67 publications
1
72
0
Order By: Relevance
“…While cold temperatures have been shown to limit the germination of Microbotryum spores in laboratory conditions (Schäfer, Kemler, Bauer, & Begerow, ), higher temperatures are more often associated with poor disease development (Alexander & Maltby, ) and global distributional studies of Microbtoryum on S. vulgaris and S. acualis have shown higher levels of disease in cooler climates (Abbate & Antonovics, ; Bueker et al., ). Declining pollinator abundance (Kearns, ) and shifts in pollinator community composition (Koski & Ashman, ) at higher elevations may provide a better explanation for the decrease in disease in the two Dianthus species at very high elevations. Indeed, a recent study of anther smut on S. latifolia along a radiation gradient near Chernobyl showed that declines in disease abundance were driven by declining pollinator abundance rather than direct negative effects of radiation on the fungus (Aguileta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…While cold temperatures have been shown to limit the germination of Microbotryum spores in laboratory conditions (Schäfer, Kemler, Bauer, & Begerow, ), higher temperatures are more often associated with poor disease development (Alexander & Maltby, ) and global distributional studies of Microbtoryum on S. vulgaris and S. acualis have shown higher levels of disease in cooler climates (Abbate & Antonovics, ; Bueker et al., ). Declining pollinator abundance (Kearns, ) and shifts in pollinator community composition (Koski & Ashman, ) at higher elevations may provide a better explanation for the decrease in disease in the two Dianthus species at very high elevations. Indeed, a recent study of anther smut on S. latifolia along a radiation gradient near Chernobyl showed that declines in disease abundance were driven by declining pollinator abundance rather than direct negative effects of radiation on the fungus (Aguileta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several lines of evidence suggest that adaptation to the local mutualist is a common feature of positive species interactions. Phenotype matching between local plant and pollinator communities is pervasive (Anderson, Johnson, & Anderson, 2009;Gómez, Abdelaziz, Camacho, Muñoz-Pajares, & Perfectti, 2009;Koski & Ashman, 2015), and a recent reciprocal translocation experiment showed that a plant's reproductive success is highest in its local pollinator community (Newman, Manning, & Anderson, 2015). In the classic mutualism between leguminous plants and nitrogen-fixing bacteria, genotype-by-genotype interactions-when fitness depends jointly on the genotypes of both partners-account for a substantial proportion of genetic variation in fitness-related traits within plant populations (Ehinger et al, 2014;Heath, 2010;Heath, Burke, & Stinchcombe, 2012).…”
mentioning
confidence: 99%
“…Patterns in the UV spectrum in particular have been shown to be under both pollinator‐mediated (Koski and Ashman ; Peterson et al. ) and abiotic selection, namely by UV irradiance (Koski and Ashman ; Koski and Ashman 2016). For traits like this we predict that the pattern of divergence will depend on the relative strength of selective forces.…”
mentioning
confidence: 99%